PENERAPAN SANKSI PIDANA TERHADAP ANAK PENYALAHGUNAAN SENJATA TAJAM STUDI DI KEPOLISIAN RESORD DOMPU - SHANDY ALQURAYVIN; NUNUNG RAHMANIA (GANEC SWARA, 2024)
Crime is a social phenomenon that is always inherent in every human life so that every development of the times will have an influence on social change in society. One of the crime phenomena that occurs due to social change is the misuse of sharp weapons by children in Dompu Regency in the jurisdiction of the Dompu Resort Police. The purpose of this study is to determine the application of sanctions against children who misuse sharp weapons in the Dompu Police Department. The research method used is a type of empirical research that examines the facts that occur in the field with a statute approach and case approach. The results showed that the application of criminal sanctions against children who misuse sharp weapons in the Dompu Resort Police was resolved by diversion through restorative justice with the result that the child was returned to the parents to be given guidance and supervision by the parents so as not to repeat their actions. In addition to diversion, children who misuse sharp weapons that are declared P21 (complete file) are forwarded to the Public Prosecutor for further processing, namely the trial stage. The Dompu Police Department, especially the Women and Children Protection Unit, has carried out its duties properly